Cerebellar Infarction in Childhood: Delayed-Onset Complication of Mild Head Trauma - OZ, Ibrahim Ilker; BOZAY OZ, Evrim; ÅžERIFOÄžLU, Ismail; KAYA, Nurullah; ERDEM, Oktay (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Oz II, Bozay Oz E, Şerifoğlu I, Kaya N, Erdem O. Cerebellar Infarction in Childhood: Delayed-Onset Complication of Mild Head Trauma. Iran J Child Neurol. Summer 2016; 10(3):82-85. Objective Cerebellar ischemic infarction is a rare complication of minor head trauma. Vertebral artery dissection, vasospasm or systemic hypo perfusion can cause infarct. However, underlying causes of the ischemic infarct cannot be explained in nearly half of cases. The accurate diagnosis is essential to ensure appropriate treatment. Here we report a five yr old boy patient of cerebellar infraction after minor head trauma, admitted to emergency serves of Bulent Ecevit University, Turkey in 2013. We aimed to remind minor head trauma that causes cerebellar infarction during childhood, and to review the important points of the diagnosis, which should be keep in mind. References Schutzman SA, Greenes DS. Pediatric minor head trauma. Ann Emerg Med 2001;37(1):65-74. Shaffer L, Rich PM, Pohl KR, Ganesan V. Can mild head injury cause ischaemic stroke? Arch Dis Child 2003;88(3):267-9. Lin JJ, Lin KL, Chou ML, Wong AM, Wang HS. Cerebellar infarction in the territory of the superior cerebellar artery in children. Pediatr Neurol 2007;37(6):435-7. Matsumoto H, Kohno K. Posttraumatic cerebral infarction due to progressive occlusion of the internal carotid artery after minor head injury in childhood: a case report. Childs Nerv Syst 2011;27(7):1169-75. Williams LS, Garg BP, Cohen M, Fleck JD, Biller J. Subtypes of ischemic stroke in children and young adults. Neurology 1997;49(6):1541-5. Kieslich M, Fiedler A, Heller C, Kreuz W, Jacobi G. Minor head injury as cause and co-factor in the aetiology of stroke in childhood: a report of eight cases. J Neurol Neurosurg Psychiatry 2002;73(1):13-6. O’Brien NF, Reuter-Rice KE, Khanna S, Peterson BM, Quinto KB. Vasospasm in children with traumatic brain injury. Intensive Care Med 2010;36(4):680-7. Barkovich A, Schwartz E. Brain and Spine Injuries in Infancy and Childhood. In: Barkovich A, Raybaud C, editors. Pediatric Neuroimaging. 5th ed. Philidelphia, PA: Lippincott Williams & Wilkins; 2012. p. 335-8. Lansberg MG, Albers GW, Beaulieu C, Marks MP. Comparison of diffusion-weighted MRI and CT in acute stroke. Neurol 2000;54(8):1557-61.